Clinical, Physiologic, and Behavioral Evaluation of Permanently Catheterized NMRI Mice - Falkenberg, Malene Kari (J Am Assoc Lab Anim Sci, 2019)
Vascular catheterization is becoming a popular technique in laboratory rodents, facilitating repetitive blood sampling and infusion in individual animals. In mice, catheterization is complicated by their small body size, which may increase the risk of postoperative complications that may both threaten catheter longevity and animal welfare. Less obvious complications to a permanent catheter may include subclinical infection, visceral tissue damage from disseminating microthrombi released from the catheter, and distress from being isolated from conspecifics and other experimental stressors. Such complications may go unnoticed and may affect animal welfare as well as confound research outcomes. This study investigated the implications of long-term arterial catheterization in NMRI mice by evaluating clinical, physiologic and behavioral parameters. Body weight and food and water consumptions were monitored during the study period. Fecal corticosterone metabolites were quantified as biomarkers of stress, and nucleic acid metabolites (8-oxo-7,8-dihydro-2’-deoxyguanisine and 8-oxo-7,8-dihydroguanosine) as biomarkers of oxidative damage. Behavioral dysfunction was studied by scoring animal welfare and nest building. Catheters were placed the right common carotid artery of mice; catheterized mice were compared with sham-operated and nonsurgical control mice. Except for an increase in the body weight of catheterized mice during the experimental period, clinical parameters (body weight and food and water consumptions) did not differ between groups. Physiologic parameters (oxidized nucleic acid metabolites and fecal corticosterone metabolites) were higher in control mice during the first week of experimentation compared with the end of study but did not differ between groups. Likewise, catheterization had no effect on behavioral parameters (nest building and animal welfare assessment). Long-term arterial catheterization of mice had no detectable implications on animal welfare in this study.